How "Natural" are Natural Monopolies in the Water Supply and Sewerage Sector? Case Studies from Developing and Transition Economies - Nauges, Céline; van den Berg, Caroline (World Bank, Washington, DC, 2012)
Using data from the International Benchmarking NETwork database, the authors estimate measures of density and scale economies in the water industry in four countries (Brazil, Colombia, Moldova, and Vietnam) that differ substantially in economic development, piped water and sewerage coverage, and characteristics of the utilities operating in the different countries. They find evidence of economies of scale in Colombia, Moldova, and Vietnam, implying the existence of a natural monopoly. In Brazil the authors cannot reject the 0 hypothesis of constant returns to scale. They also find evidence of economies of customer density in Moldova and Vietnam. The results of this study show that the cost structure of the water and wastewater sector varies significantly between countries and within countries, and over time, which has implications for how to regulate the sector.